THE INCREASING LOCAL GOVERNMENT PUBLIC VALUE THROUGH SOCIAL CAPITAL, LOCAL GOVERNMENT ENTREPRENEURIAL ACTIVITIES, AND LOCAL GOVERNMENT INNOVATION IN SITUBONDO DISTRICT - Putri, Rumanintya Lisaria; Sutrisno, Joko Sutrisno; Suprapto, Suprapto; Wahyono, Eko Wahyono; Amrulloh, Muhammad Chasan (Natapraja, 2023)
This study aims to examine the relationship between social capital and local government entrepreneurial activities on local government public value with local government innovation as an intervening variable. This study used a quantitative method with a questionnaire as a data collection tool. Data analysis technique using path analysis. The research was conducted in the city of Situbondo with the premise that the area is trying to improve and develop the concept of government innovation which aims to increase the public value of local government which is characterized by the value of regional local wisdom. The results of the direct influence analysis show that there is a positive and significant influence of social capital on local government innovation, there is a positive and significant influence of social capital on the public value of local government, there is a positive but not significant effect of local government entrepreneurial activities on local government innovation there is a positive and significant influence of local government entrepreneurial activities on local government public value and there is an influence of local government innovation on local government public value. The indirect effect analysis shows the positive and significant influence of social capital on local government public value through local government innovation. There is a positive but not significant effect shown by local government entrepreneurial activities on local government public value through local government innovation.